Kemampuan Berpikir Kritis Siswa dalam Pembelajaran Matematika melalui Pendekatan Inkuiri - Sari, Alfizah Ayu Indria; Lutfi, Ahmad (Jurnal Simki Pedagogia, 2023)
Critical thinking is an ability that must be possessed by students, especially in learning mathematics. This is because critical thinking can help reduce errors made when solving problems. The inquiry approach emphasizes the process of students thinking critically and analytically to find an answer to a problem. This study aims to discuss students' critical thinking skills in learning mathematics through the inquiry approach. This type of research is descriptive qualitative research with literature study method. Data were collected through related journals to be reviewed. The results showed that the inquiry approach has learning steps related to critical thinking skills, where students are asked to formulate problems and hypotheses, select facts & information, identify assumptions, explain solutions, evaluate, and make conclusions.